Synthesis, characterization, alkaline phosphatase inhibition assay and molecular modeling studies of 1-benzylidene-2-(4-tert- butylthiazol-2-yl) hydrazines. Issue 16 (2nd November 2021) - Aziz, Hamid; Mahmood, Abid; Zaib, Sumera; Saeed, Aamer; El-Seedi, Hesham R.; Pelletier, Julie; Sévigny, Jean; Iqbal, Jamshed
Abstract: Alkaline phosphatases are homodimeric protein enzymes which removes phosphates from several types of molecules. These catalyze the hydrolysis of monoesters in phosphoric acid which in turn catalyze a transphosphorylation reaction. Thiazoles are a privileged class of heterocyclic compounds which may potentially serve as effective phosphatase inhibitors. In this regard, the present research paper reports the facile synthesis and characterization of substituted 1-benzylidene-2-(4-tert-butylthiazol-2-yl) hydrazines with excellent yields. The synthesized compounds were tested for inhibitory potential against alkaline phosphatases. The compound 1-(4-Hydroxy, 3-methoxybenzylidene)-2-(4-tert-butylthiazol-2-yl) hydrazine (5e) was found to be the most potent inhibitor of human tissue non-alkaline phosphatase in this group of molecules with an IC50 value of 1.09 ± 0.18 µM. The compound 1-(3, 4-dimethoxybenzylidene)-2-(4-tert-butylthiazol-2-yl) hydrazine (5d) exhibited selectivity and potency for human intestinal alkaline phosphatase with an IC50 value of 0.71 ± 0.02 µM. In addition, structure activity relationship and molecular docking studies were performed to evaluate their binding modes with the target site of alkaline phosphatase. The docking analysis revealed that the most active inhibitors showed the important interactions within the binding pockets of human intestinal alkaline phosphatase and human tissue non-alkaline phosphatase and may be responsible for the inhibitory activity of the compound towards the enzymes. Therefore, the screened thiazole derivatives provided an outstanding platform for further development of alkaline phosphatase inhibitors. GRAPHICAL ABSTRACT: UF0001 Alkaline phosphatase assay revealed compound 5e (1-(4-Hydroxy, 3-methoxybenzylidene)-2-(4-tert-butylthiazol-2-yl) hydrazine) as the most active inhibitor of h -TNAP with an IC50 value of 1.09 ± 0.18 µM. Computational evaluation clearly depicts several interactions within the binding pockets of h -IAP and h -TNAP and maybe responsible for the inhibitory potential of the compound towards the enzymes. Highlights: The synthesis of 1-(benzylidene) thiosemicarbazides 3(a-i) was performed by reacting thiosemicarbazide with substituted aromatic aldehydes 1(a-i) . The synthesized 1-(benzylidene) thiosemicarbazides was cyclized with 1-chloropinacolone to obtain the respective 1-benzylidene-2-(4-tert-butylthiazol-2-yl) hydrazines 5(a-i) . The synthesized 1-benzylidene-2-(4-tert-butylthiazol-2-yl) hydrazines 5(a-i) were successfully characterized using elemental analysis, FT-IR and multi nuclear NMR. Alkaline phosphatase assay and computational study was performed in favor of the synthesized 1-benzylidene-2-(4-tert-butylthiazol-2-yl) hydrazines 5(a-i) . Communicated by Ramaswamy H. Sarma